The Public Debt Dynamics in The Philippines: Evidence from ‎ARDL and VECM Models - Camba, Aileen L. (International Journal of Accounting and Economics Studies, 2026)
This study examines the dynamics of public debt in the Philippines using the Autoregressive Distributed Lag (ARDL) and Vector Error ‎Correction Model (VECM) frameworks over the period 2005–2023. The empirical findings indicate that public debt dynamics are driven ‎predominantly by short-run macro-financial shocks rather than long-run structural factors. Although government expenditure exhibits a ‎positive coefficient in the long-run estimates, it is not statistically significant, suggesting that expenditure growth alone does not consistently ‎explain long-term debt accumulation. In contrast, the short-run results reveal strong and persistent effects of government expenditure across ‎multiple lag periods, highlighting its immediate role in shaping fiscal imbalances during crisis episodes and periods of elevated public ‎spending. Exchange rate depreciation also emerges as a significant short-run determinant, intensifying debt burdens through the valuation ‎effects of foreign-denominated liabilities. Inflation displays a nonlinear short-run impact, initially reducing the real value of debt but eventually exacerbating fiscal pressures when inflation persists. Meanwhile, stock market prices, government revenues, and interest rates do not ‎exert statistically significant effects in either the short or long run, reflecting the limited transmission of capital market signals and the gradual nature of structural revenue adjustments in the Philippine context. The policy implications underscore the importance of improving ex‎penditure efficiency, strengthening revenue mobilization, and reducing reliance on foreign-currency borrowing. The findings further high-‎light the need for credible inflation management and robust countercyclical fiscal buffers to mitigate the debt-creating effects of macroeconomic shocks. By identifying expenditure and exchange rate dynamics as key drivers of short-run debt fluctuations, this study contributes to ‎the literature on fiscal sustainability in emerging economies and offers evidence-based insights for Philippine policymakers seeking to balance growth objectives with debt stability‎.
Keywords: Public Debt; Stock Market Price; Government Expenditure; Government Revenue; Interest Rate; Exchange Rate; Inflation